2015
DOI: 10.1016/j.jmb.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Mutants of RNA Helicase DDX3X Are Defective in RNA-Stimulated ATP Hydrolysis

Abstract: The DEAD-box RNA helicase DDX3X is frequently mutated in pediatric medulloblastoma. We dissect how these mutants affect DDX3X function with structural, biochemical, and genetic experiments. We identify an N-terminal extension (“ATP-binding loop”, ABL) that is critical for the stimulation of ATP hydrolysis by RNA. We present crystal structures that suggest the ABL interacts dynamically with ATP and confirm the interaction occurs in solution by NMR chemical shift perturbation (CSP) and isothermal calorimetry (IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
93
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 59 publications
11
93
1
Order By: Relevance
“…In addition, there are regions adjacent to the helicase core conserved between DDX3, Ded1, and Vasa/DDX4 (Fig. 1A) (5,25). The N-terminal extension (NTE; residues 132-168; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, there are regions adjacent to the helicase core conserved between DDX3, Ded1, and Vasa/DDX4 (Fig. 1A) (5,25). The N-terminal extension (NTE; residues 132-168; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1B) has no predicted structure but is highly positively charged (pI ϳ12). Recent structural and biochemical work demonstrated that DDX3 constructs containing the NTE are competent for ATP hydrolysis (25), but it is unknown how this activity compares with full-length human DDX3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations